ORIGINS OF MODERN ITALIAN TOPONYMS - Lakhtionova , Catherine (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article is about the origin of Italian toponyms and their creation based on the influence of different civilizations and the appearance of the linguistic interference in setting the names of Italian toponyms. __________ References: • Falco de R. Del parlar napoletano. Colonnese editore (Napoli, 2000), 111. • Fierro, Grammatica della lingua napoletana (Milano,Rusconi libri, 1995), 278. • Granzotto, P. Perche parliamo Italiano (Firenze, Le Lettere, 1998), 151. • Pellegrini, G. B. Toponomastica italiana (Milano, HOEPLI Editore Ulrico Hoepli, 1994), 559. • Zolli, P. Come nascono le parole italiane (Milano, Rizzoli, 1989), 226.